From the history of Belarusian etymology: Rheingold Kravchuk’s prospectus - Антропаў, Мікалай (Jezikoslovni zapiski, 2018)
This article discusses a relatively unknown detail in the history of creating the Etymological Dictionary of Belarusian; namely the prospectus for this dictionary, set up by one the authors of the first volumes in the early 1970s. It analyses the composition of the prospectus, the methodology suggested for the dictionary, and other details with regard to how this process was finally realized in a real-life context.